Interseção entre o regime de bens conjugais e a ordem de vocação hereditária: uma análise hermenêutica do inciso I do artigo 1.829 do Código Civil de 2002 - Souza, Nélia de Oliveira (2021)
The present work was developed within the area of Civil Law, more specifically in an intersection between two of its sub-branches, Family Law and Inheritance Law. Its purpose was to analyze item I, of article 1,829 of CC/2002, which regulates the participation of the surviving spouse in the inheritance, in concurrence with the descendants. The issue regarding the application of the mentioned provision arises when the surviving spouse was married to the deceased in the partial communion property regime, as the doctrine debates which conditions would enable the former's participation in the inheritance and, not only that, it also diverges on the extension this participation, in this case, would reach the entire estate of the deceased or only his private assets. The dialectical approach method was used in order to present and confront the theses defended by the various currents, making comparisons between them, and these were worked through the indirect documentation search technique, in bibliographic and documentary modalities. After describing and comparing the existing doctrinal lines, this monograph presented, in the end, the understanding that, for better interpretation and application of the device in question, the interpreter should make use of the set of methods of interpreting the legal norm (hermeneutic analysis), since the use of just one of them can generate weaknesses in the thesis defended. Finally, a new wording for the aforementioned legal provision was suggested.